EFFECT OF COATING OF SYNTHETIC NPK FERTILIZER WITH PLANT GROWTH PROMOTIN BACTERIA (PGPB) ON GROWTH, YIELD OF RICE UNDER ALUM STRESS - Hai Chau, Mai; Minh Dung, Ngo (Journal of Forestry Science and Technology, 2022)
Microorganisms in the rhizosphere soil play a key role in maintaining the soil fertility, which is a key for successful crop production to meet the increasing global food demand. The aims of this study were to boost growth attributes, yield and nutrient uptake of rice by different treatment combination of plant growth promoting bacteria (PGPB) and NPK fertilizer doses. The experiment was set up as one - way factorial design (Randomized Complete Block Design), including 4 different treatments with 4 replications spreading over two seasons: winter season 2018 to 2019. The current study was done on rice cultivar (Dai Thom 8) at Long An province, a product was formulated by coating NPK with three bacterial strains of PGPB (Plant Growth Promoting Bacteria) compared the control fertilizer to improve rice productivity under a alum environment. The effects of three PGPB strains (MC/LH 2/1, SP2/LH 2/1 and ED/LH 2/1) on vegetative growth, yield of rice were tabulated. Results showed that the treatment with ASS-MC/LH2/1 produced the highest significant values of plant height, effective tiller and number of panicles per hill. The highest yield was obtained from ASS-MC/LH2/1 treatment (6.14 ton/ha), followed by ASS-SP2/LH2/1 (5.82 ton/ha). The ASS-ED/LH2/1 and control treatments recorded the lowest yield.